MYRTUS COMMUNIS AS A NATURAL ALTERNATIVE ON STRAINS OF ORAL MICROORGANISMS: STREPTOCOCCUS MUTANS AND STREPTOCOCCUS SANGUIS - Galarza Maldonado, Daysi Cristina (2016)
Objectives. Tooth decay, due to their multifactorial etiology, spark constant interest in finding new methods for controlling the causal factors of this illness. Some of the major causes are Streptococcus mutans and Streptococcus sanguis. Therefore, it was proposed to determine the effectiveness in vitro of myrtle obtained through a watery and oily process on Streptococcus mutans and Streptococcussanguis strains. Materials and methods. The minimal bactericidal concentration for each extract was determined, and the bactericidal activity through a inhibition halo count, using 0,12% chlorhexidine as a positive control and distilled water as a negative control. The microbiological tests were executed following parameters previously validated by persons trained in performing them.The results obtained were analyzed through the ANOVA test, which estimated a significance of p=0, Se encontró que todos los grupos eran diferentes entre sí, siendo el extracto oleoso el que presentó